2021
DOI: 10.3390/ijms221810165
|View full text |Cite
|
Sign up to set email alerts
|

Diversity and Taxonomic Distribution of Endophytic Bacterial Community in the Rice Plant and Its Prospective

Abstract: Endophytic bacterial communities are beneficial communities for host plants that exist inside the surfaces of plant tissues, and their application improves plant growth. They benefit directly from the host plant by enhancing the nutrient amount of the plant’s intake and influencing the phytohormones, which are responsible for growth promotion and stress. Endophytic bacteria play an important role in plant-growth promotion (PGP) by regulating the indirect mechanism targeting pest and pathogens through hydrolyti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 48 publications
(30 citation statements)
references
References 204 publications
(233 reference statements)
0
25
0
5
Order By: Relevance
“…Cry5, Cry6, Cry14, Cry21, and Cry55 are among the cry proteins that have reported nematicidal activity [ 24 ]. One of the prerequisites for a Cry protein to induce its toxic activity is that the toxin protein can be ingested into the intestine by nematodes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cry5, Cry6, Cry14, Cry21, and Cry55 are among the cry proteins that have reported nematicidal activity [ 24 ]. One of the prerequisites for a Cry protein to induce its toxic activity is that the toxin protein can be ingested into the intestine by nematodes.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have demonstrated that Cry proteins produced by Bt strains have nematicidal activity [ 16 , 23 ]. Cry proteins with nematicidal activity mainly include Cry5, Cry6, Cry14, Cry21, and Cry55 [ 14 , 24 ]; among these, the 3D-Cry protein Cry5 and non-3D-Cry protein Cry6 have been reported to kill nematodes [ 25 , 26 ]. In order to find and identify novel Cry toxins with broad-spectrum activity against insects and nematodes, we compared Bt strains GBAC46 and NMTD81 based on genome-wide screening and found three unknown Cry proteins in the GBAC46 strain.…”
Section: Introductionmentioning
confidence: 99%
“…Endophytes are microorganisms that inhabit the various tissues and organs of some or all stages of healthy plants and do not cause substantial damage to the host plant [3]. Researchers have successfully classified and reported more than 200 genera of endophytic bacteria from different plant tissues [4]. Endophytic bacteria sometimes provide multiple benefits to host plants, such as stimulation of plant growth by promoting biological nitrogen fixation, phosphate solubilization, phytohormone production (indole-3acetic acid (IAA) and gibberellins), ACC deaminase activity, and enhancing antagonism against plant pathogens [5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Bakteri endofit membantu tanaman meningkatkan penyerapan nutrisi melalui fiksasi nitrogen dari udara atau melarutkan fosfat serta memengaruhi fitohormon yang berperan sebagai pemicu pertumbuhan. Selain itu bakteri endofit secara tidak langsung memberikan manfaat bagi tanaman dengan memberikan perlindungan terhadap serangan patogen baik secara kontak maupun melalui senyawa antimikrob yang dihasilkannya (Ali et al 2021). Bakteri endofit juga dapat menempati lingkungan yang sama dengan patogen pada tanaman sehingga inokulasi bakteri endofit sebagai agens pengendali hayati dianggap sebagai metode yang tepat untuk mengendalikan patogen tanaman (Wu et al 2021).…”
Section: Pendahuluanunclassified